2003
DOI: 10.1592/phco.23.15.1558.31954
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Long‐Term Antibody Production Induced by Hepatitis B Vaccine in Patients Undergoing Hemodialysis: A Retrospective Cohort Study

Abstract: Long-term seroprevalence induced by hepatitis B vaccine was low in our patients 12 and 24 months after vaccination. These results were comparable to previously reported long-term results. Larger, prospective studies would be needed to confirm the finding that patients with diabetes had superior hepatitis B vaccine-induced antibody production at 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
7
2
Order By: Relevance
“…Our results were similar to the results of Fabrizi et al. (7), but were different from the results reported by Elwell (8), Kausz (6), and Buti et al. (5).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Our results were similar to the results of Fabrizi et al. (7), but were different from the results reported by Elwell (8), Kausz (6), and Buti et al. (5).…”
Section: Discussioncontrasting
confidence: 67%
“…In cohort 2 (40 patients), 15 (37.5%) were seropositive at 24 months. Comparison of seropositive and seronegative patients revealed no statistically significant differences in mean age, sex, serum albumin level, or eKt/V (8).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These studies were not included in our study due to a lack of a modern statistical analysis. On the other hand, four reports [27][28][29][30] did not demonstrate a relationship between failure to seroconvert after HBV vaccine and low serum albumin.…”
Section: Discussionmentioning
confidence: 89%
“…The diagnosis of diabetes mellitus in patient on hemodialysis is an independent risk factor of being non-responder to the vaccine in our study as shown in the multivariate analysis with an odd ratio of 3.15. Elwell et al [15] have shown that diabetic patients are 2.5 times more likely to respond to the vaccine. There is a discrepancy in the results between Elwell study and our study, thus additional studies and particularly prospective studies will be needed to clarify this association.…”
Section: Discussionmentioning
confidence: 99%